1986
DOI: 10.1190/1.1442152
|View full text |Cite
|
Sign up to set email alerts
|

Fluid pressure response to undrained compression in saturated sedimentary rock

Abstract: The pore pressure response of saturated porous rock subjected to undrained compression at low effective stresses are investigated theoretically and experimentally. This behavior is quantified by the undrained pore pressure buildup coefficient, [Formula: see text] where [Formula: see text] is fluid pressure, [Formula: see text] is confining pressure, and [Formula: see text] is the mass of fluid per unit bulk volume. The measured values for B for three sandstones and a dolomite arc near 1.0 at zero effective str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 4 publications
7
108
1
Order By: Relevance
“…It must be stressed that the use of Eq. (2) assumes that all constituent minerals have the same compressibility (β s ), which may not strictly be true for rocks containing both quartz and phyllosilicates (Green and Wang, 1986). Published nitrogen compressibility (β f ) data (at room temperature and Pp = 20 MPa, β f = 4.32 × 10 −8 Pa −1 ), a value of 1.2 × 10 −11 Pa −1 for compressibility of mica (β s ) independent of pressure (Birch, 1966) and the bulk framework compressibility data (β b ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It must be stressed that the use of Eq. (2) assumes that all constituent minerals have the same compressibility (β s ), which may not strictly be true for rocks containing both quartz and phyllosilicates (Green and Wang, 1986). Published nitrogen compressibility (β f ) data (at room temperature and Pp = 20 MPa, β f = 4.32 × 10 −8 Pa −1 ), a value of 1.2 × 10 −11 Pa −1 for compressibility of mica (β s ) independent of pressure (Birch, 1966) and the bulk framework compressibility data (β b ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3. In fact, since it has often been reported that most rocks have similar mechanical properties, i.e., 0.6 ≤ µ ≤ 0.85 (Byerlee 1978) and 0.7 ≤ β ≤ 1.0 (Green and Wang 1986;Berge et al 1993), which correspond to the small rectangular area in Fig. 3, we can narrow down the feasible mechanical conditions for static stress to have been a trigger to the area where the small rectangular and the white areas intersect.…”
Section: Static Stress Changes On the Fault Plane Of The Chia-yi Eartmentioning
confidence: 95%
“…Changes in the Coulomb failure stress ( ) ∆CFS transferred from the ChiChi earthquake onto the hypocenter of the Chia-Yi earthquake with various friction ( µ ) and Skempton's coefficients ( β ). The white area indicates the region with positive ∆CFS values, while the rectangular area confined by the dashed lines defines µ and β for most rocks (Byerlee 1978;Green and Wang, 1986;Berge et al 1993). The optimal µ and β values at the site of the Chia-Yi event, therefore, fall in the region where the rectangular and the white areas intersect with an average ∆CFS value of about 0.1 bar.…”
Section: Static Stress Changes On the Fault Plane Of The Chia-yi Eartmentioning
confidence: 99%
“…The text by Wang (2000) contains tables of values taken from many sources, some of which are quoted here in Table 4. One series of related contributions on the same subject includes papers by Green and Wang (1986), Berge et al (1993), Hart andWang (1995, 2001). A very useful Ph.…”
Section: Measurements Of Skempton's B Coefficientmentioning
confidence: 99%